THE RELATIONSHIP BETWEEN EXCESSIVE SCREEN TIME AND SLEEP QUALITY OF PUBLIC HEALTH STUDY PROGRAM STUDENTS AT THE DELI HUSADA HEALTH INSTITUTE DELI TUA IN 2025 - Cindy Margaretha Waruwu; Tania Fani; Winda Wardani Sembiring; Yoni Lumia Situmorang; Evita Sari Sembiring; Nada Amirah (Jurnal Kesmas Prima Indonesia, 2026)
Screen time is the time individuals spend staring at electronic device screens such as cell phones, laptops, and tablets. Meanwhile, sleep is an important physiological need to maintain physical and mental health. Poor sleep quality can affect students' daily activities and learning concentration. This study aims to determine the relationship between excessive screen time and sleep quality of students at the Faculty of Public Health at the Deli Husada Deli Tua Health Institute in 2025. This study used a cross-sectional design with a sampling technique using the Lemeshow proportion formula, resulting in 79 students as respondents. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that the majority of students had high screen time (73.4%) and poor sleep quality (74.7%). From the results of the statistical test, the Chi-Square value was 64.232 with ap value = 0.000, which indicates that there is a significant relationship between screen time and students' sleep quality. Based on these results, it can be concluded that the higher the duration of screen time, the worse the sleep quality experienced by students. Therefore, it is important to provide education to limit the time spent using electronic devices so that sleep quality can be maintained properly.